2004
DOI: 10.1103/physrevlett.92.082002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Strange Form Factors of the Nucleon fromνp,ν¯p, and Parity-Violatinge

Abstract: Determination of the strange form factors of the nucleon from νp,νp, and parity-violating ep elastic scattering A new method of obtaining the strange form factors of the nucleon is presented, in which forwardangle parity-violating ep elastic scattering data is combined with νp andνp elastic scattering data. The axial form factor in electron-nucleon scattering is complicated by the presence of electro-weak radiative corrections that in principle need to be calculated or separately measured, but this axial form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 18 publications
(22 reference statements)
2
67
0
Order By: Relevance
“…Former attempts to extract the strange axial form factor from the data [41,42] faced the fact that, as pointed out by Alberico et al [42], "the experimental uncertainty is still too large to be conclusive about specific values of the strange form factors of the nucleon" and a "rather wide range of values for the strange parameters is compatible with the BNL E734 data." The advent of new polarized electron scattering data from the above mentioned experiments changes appreciably the situation because, as shown by Pate [43,44], it allows to perform a simultaneous determination of all (electric, magnetic and axial) strange form factors with small error bars, in spite of the uncertainties of the E734 data [45]. But this is only possible in the region of 0.45 < Q 2 < 1.05 GeV 2 where the E734 differential cross sections were measured, so new NC neutrino scattering data at low Q 2 are needed for a reliable extrapolation down to Q 2 = 0.…”
Section: Neutrino-nucleon Reactionsmentioning
confidence: 99%
“…Former attempts to extract the strange axial form factor from the data [41,42] faced the fact that, as pointed out by Alberico et al [42], "the experimental uncertainty is still too large to be conclusive about specific values of the strange form factors of the nucleon" and a "rather wide range of values for the strange parameters is compatible with the BNL E734 data." The advent of new polarized electron scattering data from the above mentioned experiments changes appreciably the situation because, as shown by Pate [43,44], it allows to perform a simultaneous determination of all (electric, magnetic and axial) strange form factors with small error bars, in spite of the uncertainties of the E734 data [45]. But this is only possible in the region of 0.45 < Q 2 < 1.05 GeV 2 where the E734 differential cross sections were measured, so new NC neutrino scattering data at low Q 2 are needed for a reliable extrapolation down to Q 2 = 0.…”
Section: Neutrino-nucleon Reactionsmentioning
confidence: 99%
“…This re-analysis uses these three combinations of data to determine all three strange form factors. This results in two possible solutions at Q2 = 0.5 Gey2 summarized in Table 2.2 where Solution 1 is favored [29]. At the present time, there is only sufficient data at Q2 = 0.5 Gey2 to make such a determination.…”
Section: Combining Un and Parity-violating En Elastic Datamentioning
confidence: 89%
“…A new analysis of the BNL 734 data by Pate [29] combines low energy uN data and parity violating eN elastic scattering data from HAPPEX [30]. Using the known values for the electric, magnetic, and non-strange (CC) axial form factors of the proton and neutron, the difference of the up and Lip elastic cross sections is shown to be a function only of the strange magnetic and axial form factors, C M and CA.…”
Section: Combining Un and Parity-violating En Elastic Datamentioning
confidence: 99%
“…Details of the analysis including final estimates of systematic uncertainties can be found in references [13,12]. Finally, experimental asymmetries have been obtained for 18 Reference [14] has demonstrated that elastic νp andνp cross-sections measurements and PV ep elastic asymmetries can be combined to extract G …”
Section: G0 Forward Angle Resultsmentioning
confidence: 99%